The future development of EU exports in a global context - Robert Stehrer; Sandra M. Leitner; Roman Stöllinger (Center for Social and Economic Research (CASE), 2017)
Global trade patterns are changing rapidly. Emerging economies are increasing their share of exports overall and intensifying competition in nearly all sectors. Using a gravity-based approach, this report examines the future profile of European Union (EU) world market shares at the aggregate and sectoral level. It further points towards the changing patterns of trade within the EU. Based on the results, some conclusions on EU industrial policy are drawn.
Keywords: F14; F17; F63; 330; global trade patterns; gravity scenarios; EU industrial policy